Factors Influencing Time to Diagnosis in Childhood Narcolepsy Type 1. (July 2019) - Levy, Sarah; McArthur, Irene; Crow, Blair; Zuberi, Sameer
Objective: To study the variables impacting on time from symptom onset to diagnosis in childhood narcolepsy, including presence of cataplexy, onset in infancy, administration of the H1N1 Pandemrix vaccine, and date of diagnosis following the H1N1 pandemic. Design: A retrospective cohort study of 42 children seen in a single tertiary pediatric neurology center between 1996 and 2016. Key results: Onset of symptoms of narcolepsy occurred between infancy and 15 years, with 92.9% of children symptomatic by 13 years. Time from reported symptom onset to diagnosis ranged from 3 months to 11 years, with 51.3% diagnosed within 12 months of symptom onset. Those patients who were reportedly symptomatic from birth had a statistically significant increased time from reported symptom onset to diagnosis. Conclusions: The symptoms of childhood narcolepsy progress over time. The number of annual diagnoses in this center increased over the study period, but there is no evidence that the time from symptom onset to diagnosis is decreasing. Being reportedly symptomatic from the age of <1 year is associated with an increased time to diagnosis. We recommend raising awareness of narcolepsy among medical students and general practitioners. It is important that clinicians appreciate the clinical relevance of excessive daytime sleepiness.